2020
DOI: 10.1016/j.diabres.2020.108200
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes mellitus in 2019 novel coronavirus: A meta-analysis

Abstract: Background: Since December 2019, a new strain of coronavirus named 2019 novel coronavirus (2019-nCoV) has been discovered in Wuhan. The prevalence of diabetes mellitus, which is a great public health issue leading to immunity inhibition and an increased incidence of infections, has been increasing over the past ten years. The aim of this research was to systematically assess the prevalence of diabetes mellitus among 2019-nCoV. Methods: We searched PubMed, Embase, Web of Science and Medline for observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 29 publications
4
25
0
1
Order By: Relevance
“…3 Although people of all ages are generally susceptible to COVID-19, patients with diabetes are at higher risk for COVID-19 due to the multiple concomitant chronic diseases and immunosuppression. 4,5 According to the currently published literature, the prevalence of DM among COVID-19 patients and critically ill COVID-19 patients were 7.4-20.0% [6][7][8][9] and 17%, 10 respectively. The Chinese Center for Disease Control and Prevention (China CDC) has stipulated that COVID-19 patients discharged from hospitals are subject to a 14-day period of isolation and medical observation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although people of all ages are generally susceptible to COVID-19, patients with diabetes are at higher risk for COVID-19 due to the multiple concomitant chronic diseases and immunosuppression. 4,5 According to the currently published literature, the prevalence of DM among COVID-19 patients and critically ill COVID-19 patients were 7.4-20.0% [6][7][8][9] and 17%, 10 respectively. The Chinese Center for Disease Control and Prevention (China CDC) has stipulated that COVID-19 patients discharged from hospitals are subject to a 14-day period of isolation and medical observation.…”
Section: Introductionmentioning
confidence: 99%
“…The outbreak of this disease has resulted in an unparalleled increase in admissions to dedicated COVID-19 facilities, with diabetes, hypertension and cardiovascular disease reported to be major comorbidities among patients with COVID-19 [2]. The pooled prevalence of diabetes in a meta-analysis of nine observational studies of patients hospitalised with COVID-19 was reported to be 9% (95% confidence interval 6-12%) [3]. A high insulin requirement has been reported for the management of hyperglycaemia in patients with COVID-19, especially in those with severe disease, which has been attributed to a combination of severe insulin resistance and decreased insulin secretion due to beta-cell dysfunction [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the prevalence of diabetes (all types) in COVID-19 patients have found it to be around 10% [4,5], but it remains unclear whether people with diabetes are more susceptible to COVID-19 [6,7]. However, numerous studies have shown an increased risk of severe COVID- 19 and mortality in individuals with diabetes [4,[6][7][8][9][10][11][12], as well as higher rates of hospitalization due to COVID-19 [13,14].…”
Section: Introductionmentioning
confidence: 99%